Displays of A Different Stripe. - Pollack, J. (IEEE spectrum)
Remarkable power savings can be achieved by simply redesigning displays to provide no more information than the eye can absorb and the brain can digest. Using the strategy called biomimetic, researchers at Clairvoyante Inc. have found a way to address Bayer's color imbalance by introducing a pattern of subpixels, called the PenTile Matrix. In tests, the PenTile Matrix pattern did well on many kinds of image files, including video, computer-generated graphics, and still and moving images. The matrix did especially well displaying high-performance versions of the JPEG and MPEG-2 compression formats